2012
DOI: 10.1109/ted.2012.2220363
|View full text |Cite
|
Sign up to set email alerts
|

Local Volume Depletion/Accumulation in GAA Si Nanowire Junctionless nMOSFETs

Abstract: Abstract-In this paper, we report, for the first time, corner effect analysis in the gate-all-around equilateral triangular silicon nanowire (NW) junctionless (JL) nMOSFETs, from subthreshold to strong accumulation regime. Corners were found to accumulate and deplete more electrons than the flat sides or the channel center, when above (local accumulation) and below (local depletion) the flat-band voltage, respectively. On the contrary to the corner effect in the inversion mode (IM) devices, there is no major c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…This is due to the combination of vertical (side) and lateral (top) gates as well as corners which influences the potential distribution and gate capacitance. It has been reported that corners impact the device performance, and in particular, the capacitance above flatband [42][43][44][45][46] as the peak value of gate capacitance (in deep surface accumulation, V gs ?V fb ) has nonzero and finite contribution of corners. In a triple gate JL MOSFET with various Aspect Ratios (AR=H fin /T fin ) i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the combination of vertical (side) and lateral (top) gates as well as corners which influences the potential distribution and gate capacitance. It has been reported that corners impact the device performance, and in particular, the capacitance above flatband [42][43][44][45][46] as the peak value of gate capacitance (in deep surface accumulation, V gs ?V fb ) has nonzero and finite contribution of corners. In a triple gate JL MOSFET with various Aspect Ratios (AR=H fin /T fin ) i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The value of f in equation ( 14) is not fixed rather V gs dependent and shows significant contribution to total gate capacitance after flatband voltage. For V gs ?V fb , the majority of carriers accumulate at the corners as compared to the surface of the device [45,46] Finally, γ for TG JL transistor can be understood through the ratio of C gg(T) at V gm_avg to the maximum value of C gg(T) in the deep accumulation i.e. The gate capacitance estimated from the simplified expression (equation ( 16)) has been compared with the simulated capacitance values, and the expression provides a decent agreement for V gs >V fb for three different AR values with L g =200 nm,…”
Section: Resultsmentioning
confidence: 99%
“…In JAM‐CSG, at source–channel–drain boundaries, the carriers are accumulated similar to an ohmic contact. To understand the subthreshold behavior of the device off‐current of the device must be investigated .…”
Section: Introductionmentioning
confidence: 99%
“…Previous work focused on the planar GaAs x Sb 1−x /In y Ga 1−y As heterojunction TFETs. [13,14] Research on the performance of the SG mixed-As/Sb heterojunction TFET with cylindrical cross-section, which can eliminate the corner effect, [15] has not been found so far in the literature.…”
Section: Introductionmentioning
confidence: 99%